The Effect of Regional Original Income (PAD), Balancing Funds, Capital Expenditures and Labor on Economic Growth in the Districts/Cities of Riau Province - Nelsi Dewija Manik (Universitas Negeri Semarang, 2023)
This study aims to determine the effect of regional original income (PAD), balancing funds, capital expenditures and labor on economic growth in the districts/cities of Riau province. The data used in this study are time series and cross section data from 2017-2021, which are sourced from the Central Bureau of Statistics of Riau Province. The independent variables in this study are Local Own Revenue (PAD), Balancing Funds (DPERIMB), Capital Expenditure (BMoDAL) and Labor (TK), while the dependent variable is Economic Growth (PED). This study uses panel data with the Common Effects Model approach using the Eviews version 10 computer application program. From the results of the study it was found that Regional Original Income, Balancing Funds and Labor had a positive effect on Economic Growth in the Regency/City of Riau Province while Capital Expenditures had a negative effect on Economic Growth in the Regency/City of Riau Province. Simultaneously test Regional Original Income, Balancing Funds, Capital Expenditure and Labor together have a significant effect on Economic Growth in the Districts/Cities of Riau Province. Based on the partial test of Balancing Funds, Labor has a significant effect and Local Own Revenue, Capital Expenditures do not have a significant effect on Economic Growth in the Districts/Cities of Riau Province